2021
DOI: 10.1101/2021.04.27.441714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-outbreak surveillance strategies to support proof of freedom from foot-and-mouth disease

Abstract: Whilst emergency vaccination may help contain foot-and-mouth disease in a previously FMD-free country, its use complicates post-outbreak surveillance and the recovery of FMD-free status. A structured surveillance program is required that can distinguish between vaccinated and residually infected animals, and provide statistical confidence that the virus is no longer circulating in previously infected areas. Epidemiological models have been well-used to investigate the potential benefits of emergency vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This is driven by resourcing issues and ethical, environmental, and welfare concerns over the large-scale culling of animals (5,25,(27)(28)(29)(30). While vaccination may contribute to earlier eradication of the disease, it will be associated with additional costs-keeping vaccinated animals in the population will delay the period until FMD-free status is regained under current World Organization for Animal Health standards (13, 31) and add additional complexity to post-outbreak surveillance programs (32). This analysis has shown that many outbreaks of FMD in Australia, based on incursion scenarios identified by stakeholders, were comparatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is driven by resourcing issues and ethical, environmental, and welfare concerns over the large-scale culling of animals (5,25,(27)(28)(29)(30). While vaccination may contribute to earlier eradication of the disease, it will be associated with additional costs-keeping vaccinated animals in the population will delay the period until FMD-free status is regained under current World Organization for Animal Health standards (13, 31) and add additional complexity to post-outbreak surveillance programs (32). This analysis has shown that many outbreaks of FMD in Australia, based on incursion scenarios identified by stakeholders, were comparatively small.…”
Section: Discussionmentioning
confidence: 99%
“…That is, how can decision makers identify situations when an outbreak is likely to be large. A decision to vaccinate early in the outbreak may result in situations where it was not actually required and have consequent implications for post-outbreak surveillance, management of vaccinated animals, and regaining FMD-free status and access to export markets (31,32). Conversely, not using vaccination in some situations may lead to much larger and longer outbreaks, increased control costs, and greater impacts on industry and local communities (6).…”
Section: Discussionmentioning
confidence: 99%
“…This paper builds on recent AADIS FMD modelling studies enhancing the examination of improved surveillance tools and sampling designs for post‐outbreak management of vaccinated animals 3,20,21 . An FMD incursion scenario was developed in consultation with the local Victorian animal health authorities 5 .…”
Section: Methodsmentioning
confidence: 99%
“…This paper builds on recent AADIS FMD modelling studies enhancing the examination of improved surveillance tools and sampling designs for post‐outbreak management of vaccinated animals. 3 , 20 , 21 An FMD incursion scenario was developed in consultation with the local Victorian animal health authorities. 5 The scenario involved infection being introduced into a dairy farm in coastal southwestern Victoria in spring, under conditions expected to favour the establishment and spread of FMD.…”
Section: Methodsmentioning
confidence: 99%
“…whether structural protein tests or non‐structural protein tests are appropriate). Tests may be a clinical, serological or virological and are defined in terms of sensitivity, specificity, cost, throughput and pooling rate (Bradhurst et al., 2021a). The latter allows for the incorporation of new approaches and pooled tests such as bulk milk testing and pig salivary ropes (Armson et al., 2018; Grau et al., 2015).…”
Section: Model Overviewmentioning
confidence: 99%